Terényi Ede: Old Transylvanian Psalms for Mixed Choir. Harmonic Colour Effects Permeating the Structure. 1. Psalm-Songs - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2024)
Ede Terényi (1935-2020) was a composer of deeply religious sentiments. In his works of various genres, he often drew inspiration from religious themes, religious texts, or church hymns, regardless of the type of religion to which they were the lyrics or songs. This is also the case with his works for mixed choir, where almost half the volume has a religious theme. In it, the Old Transylvanian Psalms appear at the very top. It contains two choral works: 1. Psalm-songs and 2. Old Supplication. My present study focuses on the analysis of the first choral work, from a tonal and harmonic point of view, following the formal structure. For dramaturgical reasons, the text of the chorus is also set in parallel with the musical material.